Efficiency of treatment and use of a MDP-primer on the bond strentgh of zirconia-cement interface (Research, Society and Development, 2021)
In order to improve the adhesion between cement and zirconia, aluminum oxide sandblasting (JAT) and Rocatec, sandblasting with silica coated aluminum oxide (ROC), also the primer Signum Zirconia Bond (SZB) were used. The objective of the study was to verify the influence of the surface treatment and the presence of SZB primer in relation to the bond strength between cement and zirconia, using 60 zirconia specimens measuring 7 mm in length, 7 mm in width and 3 mm in length. thickness. Three surface treatments were evaluated: sandblasting with pre-sintering aluminum oxide (OPre), Rocatec Soft before (RPre) and zirconia final sintering (RPos), and also, regarding the presence or not of SZB. All specimens were cemented with Panavia F. The bond strength (RU) was evaluated through a shear test with a standardization device from SDI (Southern Dental Industrie) on a universal testing machine (Kratos), with a speed of 0 , 5 mm / min. The data were evaluated using Kruskal-Wallis / Mann-Whitney (α = 0.05). Average (SD) of UK without the use of SZB: OPre: 5.5 (0.9) Ba; RPre: 4.0 (1.4) Bb; RPos: 5.0 (0.5) Bab. Average (SD) of UK using SZB: OPre: 7.9 (1.5) Aab; RPre: 6.7 (2.3) Ab; RPos: 9.0 (1.2) Aa. The use of primer increased the cement / zirconia bond strength regardless of the surface treatment performed, in addition, the Rocatec group after sintering with primer, obtained higher bond strength values ​​compared to the other study groups.